Ecological niche breadth and microhabitat guild structure in temperate Australian reptiles: Implications for natural resource management in endangered grassy woodland ecosystems. (27th March 2015) - Michael, Damian R.; Kay, Geoffrey M.; Crane, Mason; Florance, Daniel; MacGregor, Christopher; Okada, Sachiko; McBurney, Lachlan; Blair, David; Lindenmayer, David B.
Abstract Ecological theory predicts that species with narrow niche requirements (habitat specialists) are more vulnerable to anthropocentric disturbances than those with broad niche requirements (habitat generalists). Hence, understanding a species ecological niche and guild membership would serve as a valuable management tool for providing a priori assessments of a species extinction risk. It also would help to forecast a species capacity to respond to land use change, as what might be expected to occur under financial incentive schemes to improve threatened ecological vegetation communities. However, basic natural history information is lacking for many terrestrial species, particularly reptiles in temperate regions of the world. To overcome this limitation, we collated 3527 reptile observations from 52 species across an endangered woodland ecoregion in south‐eastern Australia and examined ecological niche breadth and microhabitat guild structure. We found 30% of species had low ecological niche values and were classified as habitat specialists associated with large eucalypt trees, woody debris, surface rock or rocky outcrops. Cluster analysis separated species into six broad guilds based on microhabitat similarity. Approximately 80% of species belonged to guilds associated with old growth vegetation attributes or non‐renewable litho‐resources such as surface rock or rocky outcrops. Our results suggest that agri‐environment schemes that focus purely on grazing management are unlikely to provide immediate benefits to broad suites of reptiles associated with old growth vegetation and litho‐resources. Our classification scheme will be useful for identifying reptile species that are potentially vulnerable to anthropocentric disturbances and may require alternative strategies for improving habitat suitability and reptile conservation outcomes in grassy woodland ecosystems.